Quality of Health Assistants in primary Health centres in Rural Maharashtra, India - Enakshi Ganguly; Bishan S. Garg (SAGE Publishing, 2013)
Introduction Health assistants are important functionaries of the primary health care system in India. Their role is supervision of field-based services among other things. A quality assurance mechanism for these health assistants is lacking. The present study was undertaken with the objectives of developing a tool to assess the quality of health assistants in primary health centres (PHCs) and to assess their quality using this tool. Methodology Health assistants from three PHCs in the Wardha district of India were observed for a year using a tool developed from primary health care management Aavancement program modules. Data was collected by direct observation, interview, and review of records for quality of activities. Results Staff strength of health assistants was 87.5%. None of the health assistants were clear about their job descriptions. A supervisory schedule for providing supportive supervision to auxiliary nurse midwives (ANMs) was absent; most field activities pertaining to maternal and child health received poor focus. Monthly meetings lacked a clear agenda, and comments on quality improvement of services provided by the ANMs were missing. Conclusion Continuous training with sensitization on quality issues is required to improve the unsatisfactory quality.